GROWTH AND PRODUCTIVITY OF THE COMPANION CROP SYSTEM OF SWEET POTATO AND ODOT GRASS AT DIFFERENT SPACINGS - Hazna Zafira Zafira; Sutarno Sutarno; Sumarsono Sumarsono (BPFP Universitas Bengkulu, 2022)
[GROWTH AND PRODUCTIVITY OF THE COMPANION CROP SYSTEM OF SWEET POTATO AND ODOT GRASS AT DIFFERENT SPACINGS]. Odot grass cultivation still has a fairly wide space between the clumps of plants. The companion crop systems with sweet potato plants are an alternative to the use this space. The research was carried out from April 2021 to September 2021 in Kalongan Village, East Ungaran District, Semarang Regency, Central Java Province. The study was conducted in completely randomized block design (CRBD) with 2 factors and 3 replications. The first factor is spacing of the odot grasses with 2 levels, namely 90 cm x 60 cm and 90 cm x 45 cm. The second factor is spacing of sweet potato with 4 levels, namely 90 cm x 30 cm, 90 x 40 cm, 90 cm x 50 cm, dan 90 cm x 60 cm. The results of statistical analysis showed that there was no significant effect of the spacing between odot grass and sweet potato on the growth and production. However, the effect of the distance between the grass hoppers was significant (P<0.05) on the variable of the tillers and the number of sweet potato branches. The average value results showed that the number of tillers and the number of sweet potato branches between the spacing of the grasshoppers 90 cm x 60 cm was significantly higher than 90 cm x 45 cm. Odot grass can be planted together with sweet potatoes with a spacing of 90 cm between rows, 60 cm in a row of sweet potatoes, and 60 cm in a row of sweet potatoes.